Film forming body

By using latex compositions of conjugated diene polymers, sulfur vulcanizing agents and specific anti-aging agents, a film molded body with no decrease in mechanical strength during storage at high temperatures was prepared, which solved the problem of the mechanical strength of the impregnated molded body at high temperatures in the prior art, and achieved the improvement of the high temperature stability and mechanical properties of the film molded body.

CN115803387BActive Publication Date: 2025-04-11ZEON CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202180049573.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-07-29
Filing Date
2021-07-02
Publication Date
2025-04-11
Estimated Expiration
2041-07-02

AI Technical Summary

Technical Problem

The mechanical strength of the existing impregnated molded bodies is reduced during storage at high temperatures, making it difficult to meet the strict demand characteristics.

Method used

A latex composition containing a conjugated diene polymer was prepared by combining a sulfur-based vulcanizing agent, a vulcanizing promoter and a specific anti-aging agent to prepare a film molded body with a thickness of 20 to 300 μm.

Benefits of technology

It effectively suppresses the reduction of the mechanical strength of the film molded body during storage at high temperature, and maintains excellent tensile strength and tear strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004048223540000311
    Figure BDA0004048223540000311
Patent Text Reader

Abstract

The present invention provides a film-forming body, which is a film-forming body with a thickness of 20 to 300 μm obtained by using a latex composition containing a conjugated diene polymer latex, a sulfur-based vulcanizing agent, a vulcanization accelerator, and an antioxidant, wherein the antioxidant is at least one selected from a phenolic antioxidant and a quinoline antioxidant, and the molecular weight of the antioxidant is 300 to 600.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a film formed body. Background Art

[0002] Conventionally, it is known that a dip-molded composition containing rubber latex is dip-molded to obtain a film-molded body such as a pacifier, balloon, glove, airbag, bag, etc., which is used in contact with the human body. From the viewpoint of being preferably used for these purposes, the film-molded body such as the dip-molded body is required to have excellent tensile strength.

[0003] For example, Patent Document 1 discloses a dip-molded article obtained by dip-molding a dip-molding composition containing synthetic polyisoprene latex, a sulfur-based vulcanizing agent, zinc oxide, a vulcanization accelerator, a specific dispersant, and a specific amount of a monovalent salt of a dithiocarbamic acid. The technique of Patent Document 1 can obtain a dip-molded article having excellent tensile strength.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2011-219543. Summary of the invention

[0007] Problem that the invention aims to solve

[0008] On the other hand, in recent years, the demand for film-molded products such as impregnated products has become stricter, and there is a demand for impregnated products such as film-molded products that can suppress the reduction of mechanical strength when stored at high temperatures (e.g., around 70° C.). The present invention has been made in view of such actual conditions, and an object of the present invention is to provide a film-molded product that can suppress the reduction of mechanical strength when stored at high temperatures.

[0009] Solutions for solving problems

[0010] The present inventors have conducted intensive research to achieve the above-mentioned purpose and have found that a film-molded body obtained by using a latex composition containing a conjugated diene polymer, a crosslinking agent, a crosslinking accelerator, and an antioxidant having a specific structure and molecular weight can suppress the reduction in mechanical strength during high-temperature storage, thereby completing the present invention.

[0011] That is, according to the present invention, a film molding can be provided, which is a film molding with a thickness of 20 to 300 μm obtained using a latex composition, wherein the latex composition contains a latex of a conjugated diene polymer, a sulfur-based vulcanizing agent, a vulcanization accelerator, and an antioxidant, wherein the antioxidant is at least one selected from a phenolic antioxidant and a quinoline antioxidant, and the molecular weight of the antioxidant is 300 to 600.

[0012] In the film formed article of the present invention, it is preferred that the antioxidant contains at least an aromatic compound (a) having two or more phenolic hydroxyl groups.

[0013] In the film formed article of the present invention, it is preferred that the antioxidant contains at least an aromatic compound (a-1) having two or more hindered phenol structures.

[0014] In the film formed article of the present invention, it is preferred that the antioxidant contains at least an aromatic compound (a-2) having two or more hindered phenol structures and a diphenylmethane skeleton.

[0015] In the film formed article of the present invention, the antioxidant preferably includes an aromatic compound (a) having two or more phenolic hydroxyl groups and an aromatic compound (b-1) having one phenolic hydroxyl group and one or more -NH- bonds.

[0016] In the film formed article of the present invention, the latex of the conjugated diene polymer is preferably a latex of synthetic polyisoprene, a latex of a styrene-isoprene-styrene block copolymer, or a latex of natural rubber.

[0017] In the film formed article of the present invention, the latex of the conjugated diene polymer is preferably a latex of a carboxyl group-modified conjugated diene polymer.

[0018] In the film formed article of the present invention, it is preferred that the conjugated diene polymer has a swelling index (SI) of 105 to 300%.

[0019] In the film molded product of the present invention, the content of the sulfur-based vulcanizing agent in the latex composition is preferably 0.1 to 1.2 parts by weight based on 100 parts by weight of the conjugated diene polymer in the latex composition.

[0020] In the film formed article of the present invention, it is preferred that the cross-linking accelerator is a xanthogenic acid compound.

[0021] Effects of the Invention

[0022] According to the present invention, it is possible to provide a film formed body in which a decrease in mechanical strength during storage at high temperatures is suppressed. DETAILED DESCRIPTION

[0023] The film-formed product of the present invention is obtained using a latex composition containing a conjugated diene polymer latex, a sulfur-based vulcanizing agent, a vulcanization accelerator, and an antioxidant having a specific structure and molecular weight.

[0024] The present inventors have conducted research and found that even a film molded body having excellent mechanical properties such as tensile strength and tear strength at room temperature has a problem that the mechanical strength of the film molded body is greatly reduced when the film is stored at a high temperature (for example, about 70°C) when the film thickness is as thin as 20 to 300 μm. In addition, in order to suppress the reduction of the mechanical strength of a film molded body having a film thickness as thin as 20 to 300 μm when stored at a high temperature (for example, about 70°C), the present inventors have conducted intensive research and found that a film molded body obtained by using a latex composition containing a conjugated diene polymer latex, a crosslinking agent, a crosslinking accelerator, and an antioxidant having a specific structure and molecular weight can achieve the above-mentioned purpose, thereby completing the present invention.

[0025] <Latex composition>

[0026] The latex composition used in the present invention contains a latex of a conjugated diene polymer.

[0027] The conjugated diene polymer constituting the latex of the conjugated diene polymer is not particularly limited, and examples thereof include synthetic polyisoprene, styrene-isoprene-styrene block copolymer (SIS), natural rubber (including natural rubber from which protein has been removed), etc. As the conjugated diene polymer, synthetic polyisoprene, styrene-isoprene-styrene block copolymer (SIS) or natural rubber (including natural rubber from which protein has been removed) is preferred, synthetic polyisoprene, styrene-isoprene-styrene block copolymer (SIS) or natural rubber from which protein has been removed is more preferred, synthetic polyisoprene or styrene-isoprene-styrene block copolymer (SIS) is further preferred, and synthetic polyisoprene is particularly preferred.

[0028] When synthetic polyisoprene is used as the conjugated diene polymer, the synthetic polyisoprene may be a homopolymer of isoprene or a copolymer obtained by copolymerizing with other ethylenically unsaturated monomers copolymerizable with isoprene. The content of isoprene units in the synthetic polyisoprene relative to all monomer units is preferably 70% by weight or more, more preferably 90% by weight or more, further preferably 95% by weight or more, and particularly preferably 100% by weight (homopolymer of isoprene). By making the content of isoprene units in the synthetic polyisoprene within the above range, the reduction in mechanical strength of the film molded body of the present invention when stored at high temperatures can be further suppressed.

[0029] Examples of other ethylenically unsaturated monomers copolymerizable with isoprene include conjugated diene monomers other than isoprene, such as butadiene, chloroprene, and 1,3-pentadiene; ethylenically unsaturated nitrile monomers such as acrylonitrile, methacrylonitrile, fumaronitrile, and α-chloroacrylonitrile; vinyl aromatic monomers such as styrene and alkylstyrene; ethyl (meth)acrylate (meaning "methyl acrylate and / or methyl methacrylate", and the same also applies to ethyl (meth)acrylate, etc.), ethyl (meth)acrylate, butyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate, etc. These other ethylenically unsaturated monomers copolymerizable with isoprene may be used alone or in combination of two or more.

[0030] Synthetic polyisoprene can be obtained by a conventionally known method, for example, using a Ziegler polymerization catalyst formed by trialkylaluminum-titanium tetrachloride, an alkyllithium polymerization catalyst such as n-butyllithium and sec-butyllithium, in an inactive polymerization solvent, isoprene and other ethylenically unsaturated monomers that can be copolymerized as needed are subjected to solution polymerization to obtain the same. The polymer solution of synthetic polyisoprene obtained by solution polymerization can be directly made into a latex of synthetic polyisoprene, or solid-state synthetic polyisoprene can be taken out from the polymer solution and dissolved in an organic solvent to make a latex of synthetic polyisoprene. In addition, in the case of obtaining a polymer solution of synthetic polyisoprene by the above method, impurities such as residues of the polymerization catalyst remaining in the polymer solution can be removed. In addition, an antioxidant described later can also be added to the solution during or after the polymerization. In addition, commercially available solid-state synthetic polyisoprene can also be used.

[0031] The isoprene units in the synthetic polyisoprene include four types, namely, cis-bonded units, trans-bonded units, 1,2-vinyl-bonded units, and 3,4-vinyl-bonded units, depending on the bonding state of the isoprene. From the viewpoint of improving the tensile strength of the obtained film-molded product such as the impregnated molded product, the content ratio of the cis-bonded units in the isoprene units contained in the synthetic polyisoprene is preferably 70% by weight or more, more preferably 90% by weight or more, and even more preferably 95% by weight or more relative to the total isoprene units.

[0032] The weight average molecular weight of the synthetic polyisoprene is preferably 10,000 to 5,000,000, more preferably 500,000 to 5,000,000, and even more preferably 800,000 to 3,000,000, calculated as standard polystyrene by gel permeation chromatography. By setting the weight average molecular weight of the synthetic polyisoprene to be within the above range, the decrease in mechanical strength of the film molded product of the present invention when stored at high temperatures can be further suppressed, and there is a tendency that the synthetic polyisoprene latex can be easily produced.

[0033] Furthermore, the polymer Mooney viscosity (ML1+4, 100° C.) of the synthetic polyisoprene is preferably 50 to 85, more preferably 60 to 85, and even more preferably 70 to 85.

[0034] Examples of methods for obtaining synthetic polyisoprene latex include: (1) a method for producing synthetic polyisoprene latex by emulsifying a solution or microsuspension of synthetic polyisoprene dissolved or finely dispersed in an organic solvent in water in the presence of an anionic surfactant and removing the organic solvent as needed; (2) a method for directly producing synthetic polyisoprene latex by emulsion polymerization or suspension polymerization of isoprene alone or a mixture of isoprene and an ethylenically unsaturated monomer copolymerizable therewith in the presence of an anionic surfactant. The production method (1) is preferred because synthetic polyisoprene having a high ratio of cis-bonded units in the isoprene units can be used and a decrease in the mechanical strength of the film-molded product of the present invention when stored at high temperatures can be further suppressed.

[0035] Examples of the organic solvent used in the production method (1) include aromatic hydrocarbon solvents such as benzene, toluene, and xylene; alicyclic hydrocarbon solvents such as cyclopentane, cyclopentene, cyclohexane, and cyclohexene; aliphatic hydrocarbon solvents such as pentane, hexane, and heptane; and halogenated hydrocarbon solvents such as dichloromethane, chloroform, and dichloroethane. Among these, alicyclic hydrocarbon solvents are preferred, and cyclohexane is particularly preferred.

[0036] The amount of the organic solvent used is preferably 2000 parts by weight or less, more preferably 20 to 1500 parts by weight, and even more preferably 500 to 1500 parts by weight, based on 100 parts by weight of the synthetic polyisoprene.

[0037] Examples of the anionic surfactant used in the production method (1) include fatty acid salts such as sodium laurate, potassium myristate, sodium palmitate, potassium oleate, sodium linolenate, and sodium rosinate; alkylbenzene sulfonates such as sodium dodecylbenzene sulfonate, potassium dodecylbenzene sulfonate, sodium decylbenzene sulfonate, potassium decylbenzene sulfonate, sodium hexadecylbenzene sulfonate, and potassium hexadecylbenzene sulfonate; alkyl sulfosuccinates such as sodium di(2-ethylhexyl)sulfosuccinate, potassium di(2-ethylhexyl)sulfosuccinate, and sodium dioctylsulfosuccinate; alkyl sulfate ester salts such as sodium lauryl sulfate and potassium lauryl sulfate; polyoxyethylene alkyl ether sulfate ester salts such as sodium polyoxyethylene lauryl ether sulfate and potassium polyoxyethylene lauryl ether sulfate; monoalkyl phosphates such as sodium lauryl phosphate and potassium lauryl phosphate, and the like.

[0038] Among these anionic surfactants, fatty acid salts, alkylbenzenesulfonates, alkylsulfosuccinates, alkyl sulfate ester salts, and polyoxyethylene alkyl ether sulfate ester salts are preferred, and fatty acid salts and alkylbenzenesulfonates are particularly preferred.

[0039] In addition, from the viewpoint of being able to more effectively remove the trace amount of residual polymerization catalyst (particularly aluminum and titanium) from the synthetic polyisoprene and suppressing the generation of coagulants when producing the conjugated diene polymer latex composition, it is preferred to use at least one selected from alkylbenzene sulfonate, alkyl sulfosuccinate, alkyl sulfate ester salt and polyoxyethylene alkyl ether sulfate ester salt together with a fatty acid salt, and it is particularly preferred to use an alkylbenzene sulfonate together with a fatty acid salt. Here, as the fatty acid salt, sodium rosinate and potassium rosinate are preferred, and as the alkylbenzene sulfonate, sodium dodecylbenzene sulfonate and potassium dodecylbenzene sulfonate are preferred. In addition, these surfactants may be used alone or in combination of two or more.

[0040] In addition, as described above, by using at least one selected from alkylbenzene sulfonates, alkyl sulfosuccinates, alkyl sulfate esters and polyoxyethylene alkyl ether sulfate esters and a fatty acid salt in combination, the obtained latex contains at least one selected from alkylbenzene sulfonates, alkyl sulfosuccinates, alkyl sulfate esters and polyoxyethylene alkyl ether sulfate esters and a fatty acid salt.

[0041] In the production method of (1) above, a surfactant other than anionic surfactants may be used in combination. Examples of such surfactants other than anionic surfactants include copolymerizable surfactants such as sulfonates of α,β-unsaturated carboxylic acids, sulfates of α,β-unsaturated carboxylic acids, and sulfoalkyl aryl ethers.

[0042] The amount of the anionic surfactant used in the production method of (1) is preferably 0.1 to 50 parts by weight, more preferably 0.5 to 30 parts by weight, relative to 100 parts by weight of the synthetic polyisoprene. In addition, when two or more surfactants are used, it is preferred that their total amount be within the above range. That is, for example, when at least one selected from alkylbenzene sulfonate, alkyl sulfosuccinate, alkyl sulfate ester salt and polyoxyethylene alkyl ether sulfate ester salt is used in combination with a fatty acid salt, it is preferred that their total amount be within the above range.

[0043] In addition, when at least one selected from alkylbenzene sulfonates, alkyl sulfosuccinates, alkyl sulfate esters and polyoxyethylene alkyl ether sulfate esters and fatty acid salts are used in combination as anionic surfactants, their usage ratio is preferably in the range of 1:1 to 10:1, and more preferably in the range of 1:1 to 7:1, calculated by the weight ratio of "fatty acid salt" : "total of at least one surfactant selected from alkylbenzene sulfonates, alkyl sulfosuccinates, alkyl sulfate esters and polyoxyethylene alkyl ether sulfate esters".

[0044] The amount of water used in the production method (1) is preferably 10 to 1000 parts by weight, more preferably 30 to 500 parts by weight, and most preferably 50 to 100 parts by weight, relative to 100 parts by weight of the organic solvent solution of the synthetic polyisoprene. Examples of the type of water used include hard water, soft water, ion-exchanged water, distilled water, and zeolite water, with soft water, ion-exchanged water, and distilled water being preferred.

[0045] The apparatus for emulsifying a solution or microsuspension of synthetic polyisoprene dissolved or microdispersed in an organic solvent in water in the presence of an anionic surfactant can be used without particular limitation as long as it is an emulsifier or disperser generally available on the market. The method for adding the anionic surfactant to the solution or microsuspension of synthetic polyisoprene is not particularly limited, and the anionic surfactant may be added to water in advance, to the solution or microsuspension of synthetic polyisoprene in advance, or to both in advance, or may be added to the emulsion during the emulsification operation, and may be added all at once or in batches.

[0046] Examples of the emulsifying apparatus include batch emulsifiers such as "Homogenizer" (manufactured by Aika Co., Ltd.), "Polytron" (manufactured by Kinematica Co., Ltd.), and "TK Automatic Homomixer" (manufactured by Tokushu Kika Kogyo Co., Ltd.); continuous emulsifiers such as "TK Line Homomixer" (manufactured by Tokushu Kika Kogyo Co., Ltd.), "Colloid Mill" (manufactured by Kobelco Pantec Co., Ltd.), "Thrasher" (manufactured by Nippon Coking Industry Co., Ltd.), "Trigonal Wet Micro-Pulverizer" (manufactured by Mitsui Miike Chemical Industry Co., Ltd.), "Cavitron" (manufactured by Eurotec Co., Ltd.), "Milder" (manufactured by Pacific Machinery Co., Ltd.), and "Fine Flow Mill" (manufactured by Pacific Machinery Co., Ltd.); and microfluidizers such as "Microfluidizer" (manufactured by Minoga Industry Co., Ltd.), "Nanomizer" (manufactured by Neomer Corporation), and "APV Gaulin" (manufactured by Gaulin Co., Ltd.); membrane emulsifiers such as the trade name "membrane emulsifier" (manufactured by Reika Industry Co., Ltd.); vibration emulsifiers such as the trade name "vibration mixer" (manufactured by Reika Industry Co., Ltd.); ultrasonic emulsifiers such as the trade name "ultrasonic homogenizer" (manufactured by Branson Co., Ltd.). In addition, the conditions for the emulsification operation using the emulsification device are not particularly limited, and the treatment temperature, treatment time, etc. can be appropriately selected to achieve the desired dispersion state.

[0047] In the manufacturing method of (1) above, it is desirable to remove the organic solvent from the emulsion obtained by the emulsification operation. As a method for removing the organic solvent from the emulsion, a method is preferably used that can reduce the content of the organic solvent (preferably alicyclic hydrocarbon solvent) in the obtained synthetic polyisoprene latex to 500 ppm by weight or less, and methods such as reduced pressure distillation, atmospheric distillation, steam distillation, centrifugal separation, etc. can be used.

[0048] Furthermore, after the organic solvent is removed, in order to increase the solid content concentration of the synthetic polyisoprene latex, a concentration operation may be carried out by a method such as reduced pressure distillation, atmospheric pressure distillation, centrifugal separation, membrane concentration, etc., as necessary. In particular, centrifugal separation is preferably carried out from the viewpoint of being able to increase the solid content concentration of the synthetic polyisoprene latex and reduce the residual amount of the surfactant in the synthetic polyisoprene latex.

[0049] As for centrifugal separation, for example, a continuous centrifuge can be used to obtain the synthetic polyisoprene latex as a light liquid after centrifugal separation, and the centrifugal separation is preferably carried out under the following conditions: the centrifugal force is preferably 100 to 10,000 G, the solid content concentration of the synthetic polyisoprene latex before centrifugal separation is preferably 2 to 15% by weight, the flow rate fed to the centrifuge is preferably 500 to 1,700 kg / hour, and the back pressure (gauge pressure) of the centrifuge is preferably 0.03 to 1.6 MPa. In addition, the residual amount of the surfactant in the synthetic polyisoprene latex can be reduced by this.

[0050] The solid content concentration of the synthetic polyisoprene latex is preferably 30 to 70% by weight, more preferably 40 to 70% by weight. When the solid content concentration is within the above range, the latex viscosity becomes appropriate and the latex becomes easy to handle.

[0051] The volume average particle size of the synthetic polyisoprene latex is preferably 0.1 to 10 μm, more preferably 0.5 to 3 μm, and even more preferably 0.5 to 2.0 μm. By setting the volume average particle size within the above range, the latex viscosity becomes moderate, the handling becomes easy, and the formation of a film on the surface of the latex can be suppressed when the synthetic polyisoprene latex is stored.

[0052] In addition, the synthetic polyisoprene latex may be formulated with additives such as pH adjusters, defoamers, preservatives, crosslinking agents, chelating agents, deoxidizers, and dispersants that are commonly formulated in the latex field. Examples of the pH adjuster include: alkali metal hydroxides such as sodium hydroxide and potassium hydroxide; alkali metal carbonates such as sodium carbonate and potassium carbonate; alkali metal bicarbonates such as sodium bicarbonate; ammonia; organic amine compounds such as trimethylamine and triethanolamine, etc., preferably alkali metal hydroxides or ammonia.

[0053] As the conjugated diene polymer, a styrene-isoprene-styrene block copolymer (SIS) can be used as described above. In SIS, "S" represents a styrene block, and "I" represents an isoprene block.

[0054] SIS can be obtained by a conventionally known method, for example, using an active organic metal such as n-butyl lithium as an initiator, and copolymerizing isoprene and styrene blocks in an inactive polymerization solvent to obtain SIS. Moreover, the polymer solution of SIS obtained can be directly used for the manufacture of SIS latex, or solid SIS can be taken out from the polymer solution and then dissolved in an organic solvent for the manufacture of SIS latex. There is no particular limitation on the method for manufacturing SIS latex, but the following method is preferred: in the presence of a surfactant, a solution or microsuspension of SIS dissolved or microdispersed in an organic solvent is emulsified in water, and the organic solvent is removed as needed to manufacture SIS latex. At this time, impurities such as residues of the polymerization catalyst remaining in the polymer solution after synthesis can also be removed. In addition, an antioxidant described later can also be added to the solution during or after polymerization. In addition, commercially available solid SIS can also be used.

[0055] As the organic solvent, the same solvent as in the case of synthesizing polyisoprene can be used, preferably an aromatic hydrocarbon solvent and an alicyclic hydrocarbon solvent, particularly preferably cyclohexane and toluene. In addition, the amount of the organic solvent used is usually 50 to 2000 parts by weight, preferably 80 to 1000 parts by weight, more preferably 100 to 500 parts by weight, and further preferably 150 to 300 parts by weight, relative to 100 parts by weight of SIS.

[0056] Examples of the surfactant include the same surfactants as those in the case of synthesizing polyisoprene described above, and anionic surfactants are preferred, with sodium rosinate and sodium dodecylbenzenesulfonate being particularly preferred.

[0057] The amount of the surfactant used is preferably 0.1 to 50 parts by weight, more preferably 0.5 to 30 parts by weight, based on 100 parts by weight of SIS.

[0058] The amount of water used in the method for producing the SIS latex is preferably 10 to 1000 parts by weight, more preferably 30 to 500 parts by weight, and most preferably 50 to 100 parts by weight, relative to 100 parts by weight of the organic solvent solution of SIS. Examples of the type of water used include hard water, soft water, ion exchange water, distilled water, zeolite water, etc. In addition, a polar solvent represented by an alcohol such as methanol may be used in combination with water.

[0059] As a method for adding the monomer, the same method as in the case of synthesizing polyisoprene described above can be exemplified. In addition, as an apparatus for emulsifying an organic solvent solution or microsuspension of SIS in water in the presence of a surfactant, the same apparatus as in the case of synthesizing polyisoprene described above can be exemplified. The method for adding the surfactant is not particularly limited, and the surfactant may be added to water in advance, to a solution or microsuspension of SIS in advance, or to both in advance, or may be added to the emulsion during the emulsification operation, or may be added all at once or in batches.

[0060] In the above-mentioned method for producing SIS latex, it is preferred to obtain SIS latex by removing the organic solvent from the emulsified product obtained by emulsification. The method for removing the organic solvent from the emulsified product is not particularly limited, and methods such as vacuum distillation, atmospheric distillation, steam distillation, centrifugal separation, etc. can be used.

[0061] After the organic solvent is removed, if necessary, in order to increase the solid content concentration of the SIS latex, a concentration operation may be carried out by a method such as reduced pressure distillation, normal pressure distillation, centrifugal separation, membrane concentration, etc.

[0062] The solid content concentration of the SIS latex is preferably 30 to 70% by weight, more preferably 50 to 70% by weight. When the solid content concentration is within the above range, the latex viscosity becomes appropriate and the latex becomes easy to handle.

[0063] In addition, the SIS latex may be formulated with additives commonly used in the latex field, such as pH adjusters, defoamers, preservatives, crosslinking agents, chelating agents, deoxidizers, dispersants, and antioxidants. Examples of the pH adjuster include the same pH adjusters as those for the synthetic polyisoprene, preferably alkali metal hydroxides or ammonia.

[0064] In the SIS latex thus obtained, the content of styrene units in the styrene blocks relative to the total monomer units is preferably 70 to 100% by weight, more preferably 90 to 100% by weight, and further preferably 100% by weight. In addition, in the SIS, the content of isoprene units in the isoprene blocks relative to the total monomer units is preferably 70 to 100% by weight, more preferably 90 to 100% by weight, and further preferably 100% by weight.

[0065] The content ratio of styrene units to isoprene units in SIS is generally 1:99 to 90:10, preferably 3:97 to 70:30, more preferably 5:95 to 50:50, and even more preferably 10:90 to 30:70, in terms of the weight ratio of "styrene units:isoprene units".

[0066] The weight average molecular weight of SIS is preferably 10,000 to 1,000,000, more preferably 50,000 to 500,000, and even more preferably 100,000 to 300,000, in terms of standard polystyrene analyzed by gel permeation chromatography. When the weight average molecular weight of SIS is within the above range, it tends to be easy to produce a latex of SIS.

[0067] The volume average particle size of the latex particles (SIS particles) in the SIS latex is preferably 0.1 to 10 μm, more preferably 0.5 to 3 μm, and even more preferably 0.5 to 2.0 μm. By setting the volume average particle size of the latex particles within the above range, the latex viscosity becomes moderate, making it easier to handle, and when storing the SIS latex, the formation of a film on the latex surface can be suppressed.

[0068] In addition, as the conjugated diene polymer, natural rubber can also be used as described above. As the natural rubber latex, latex obtained from a natural rubber tree and latex obtained by treating the latex can be used, for example, field latex collected from a natural rubber tree, commercially available natural rubber latex obtained by treating field latex with ammonia or the like can be used.

[0069] In addition, as a conjugated diene polymer, a natural rubber from which protein has been removed can also be used. Since the natural rubber from which protein has been removed has removed the protein that causes the symptoms of immediate allergy (type I), the obtained film-formed body can be preferably used for purposes such as pacifiers, balloons, gloves, air bags, bags, etc. that are used in contact with the human body. There is no particular limitation on the method for obtaining the latex of natural rubber from which protein has been removed. For natural rubber latex, a urea compound is reacted in the presence of a surfactant, thereby modifying the protein contained in the natural rubber, and then the natural rubber latex containing such modified protein is subjected to centrifugal separation, coagulation of the rubber component, ultrafiltration, and other treatments, thereby separating the natural rubber and the modified protein, removing the modified protein, and thus obtaining the latex of natural rubber from which protein has been removed.

[0070] In addition, as the conjugated diene polymer, as described above, synthetic polyisoprene, styrene-isoprene-styrene block copolymer (SIS), natural rubber (including natural rubber from which protein has been removed), etc. can be used, but are not limited to these, and nitrile-containing conjugated diene copolymers, butadiene polymers, styrene-butadiene copolymers, etc. can be used.

[0071] In addition, from the perspective of further suppressing the reduction in mechanical strength of the film-formed product of the present invention when stored at high temperatures, the conjugated diene polymer is preferably a carboxyl-modified conjugated diene polymer modified with a carboxyl group. The carboxyl-modified conjugated diene polymer can be obtained by modifying the above-mentioned conjugated diene polymer with a monomer having a carboxyl group.

[0072] There is no particular limitation on the method of modifying the conjugated diene polymer using a monomer having a carboxyl group, and examples thereof include a method of graft-polymerizing the monomer having a carboxyl group to the conjugated diene polymer in an aqueous phase. There is no particular limitation on the method of graft-polymerizing the monomer having a carboxyl group to the conjugated diene polymer in an aqueous phase, and a conventionally known method may be used, and preferably the following method: after adding a monomer having a carboxyl group and an organic peroxide to a latex of a conjugated diene polymer, the monomer having a carboxyl group and the conjugated diene polymer are reacted in an aqueous phase.

[0073] The organic peroxide is not particularly limited, and examples thereof include diisopropylbenzene hydroperoxide, cumene hydroperoxide, tert-butyl hydroperoxide, 1,1,3,3-tetramethylbutyl hydroperoxide, di-tert-butyl peroxide, isobutyryl peroxide, benzoyl peroxide, etc. From the viewpoint of improving the mechanical strength of the obtained film molding, 1,1,3,3-tetramethylbutyl hydroperoxide is particularly preferred. These organic peroxides may be used alone or in combination of two or more.

[0074] The amount of the organic peroxide added is not particularly limited, but is preferably 0.01 to 3 parts by weight, more preferably 0.1 to 1 part by weight, based on 100 parts by weight of the conjugated diene polymer contained in the latex of the conjugated diene polymer.

[0075] In addition, the organic peroxide can be combined with a reducing agent and used as a redox polymerization initiator. The reducing agent is not particularly limited, and examples thereof include compounds containing metal ions in a reduced state such as ferrous sulfate and cuprous naphthenate; sulfinates such as sodium hydroxymethanesulfinate; amine compounds such as dimethylaniline, etc. These reducing agents may be used alone or in combination of two or more.

[0076] The amount of the reducing agent added is not particularly limited, but is preferably 0.01 to 1 part by weight relative to 1 part by weight of the organic peroxide.

[0077] The method for adding the organic peroxide and the reducing agent is not particularly limited, and known methods such as all-at-once addition, batch addition, and continuous addition can be used.

[0078] The reaction temperature when reacting the conjugated diene polymer and the monomer having a carboxyl group is not particularly limited, but is preferably 15 to 80° C., more preferably 30 to 50° C. The reaction time when reacting the conjugated diene polymer and the monomer having a carboxyl group can be appropriately set depending on the reaction temperature, but is preferably 30 to 300 minutes, more preferably 60 to 120 minutes.

[0079] The solid content concentration of the latex of the conjugated diene polymer when the conjugated diene polymer and the monomer having a carboxyl group are reacted is not particularly limited, but is preferably 5 to 60% by weight, and more preferably 10 to 40% by weight.

[0080] As the monomer with carboxyl group, for example, can be cited: ethylenically unsaturated monocarboxylic acid monomers such as acrylic acid and methacrylic acid; ethylenically unsaturated polycarboxylic acid monomers such as itaconic acid, maleic acid, fumaric acid, butene tricarboxylic acid; partial ester monomers of ethylenically unsaturated polycarboxylic acids such as monobutyl fumarate, monobutyl maleate, maleic acid mono-2-hydroxypropyl ester; polycarboxylic acid anhydrides such as maleic anhydride and citraconic anhydride, etc., from the aspect of making the effect brought by carboxyl modification more significant, preferably ethylenically unsaturated monocarboxylic acid monomers, particularly preferably acrylic acid and methacrylic acid. In addition, these monomers can be used alone or in combination of two or more. In addition, the above-mentioned carboxyl group also includes a carboxyl group that forms a salt with an alkali metal, ammonia, etc.

[0081] The amount of the monomer having a carboxyl group used is preferably 0.01 to 100 parts by weight, more preferably 0.01 to 40 parts by weight, and further preferably 0.5 to 20 parts by weight, based on 100 parts by weight of the conjugated diene polymer.

[0082] The method of adding the monomer having a carboxyl group to the latex of the conjugated diene polymer is not particularly limited, and a known addition method such as all-at-once addition, batch addition, or continuous addition can be adopted.

[0083] The modification rate of the monomer having a carboxyl group in the carboxyl-modified conjugated diene polymer can be appropriately controlled according to the purpose of use of the obtained conjugated diene polymer latex composition, preferably 0.01 to 10% by weight, more preferably 0.2 to 5% by weight, further preferably 0.3 to 3% by weight, and particularly preferably 0.4 to 2% by weight. By making the modification rate of the monomer having a carboxyl group within the above range, the viscosity of the latex of the obtained conjugated diene polymer becomes more appropriate, easy to transport, and can further suppress the reduction of the mechanical strength of the film molding of the present invention when stored at high temperature. In addition, the modification rate is expressed by the following formula.

[0084] Modification rate (weight %) = (X / Y) × 100

[0085] In the above formula, X represents the weight of the monomer unit having a carboxyl group in the carboxyl-modified conjugated diene polymer, and Y represents the weight of the carboxyl-modified conjugated diene polymer. 1 H-NMR determination, by 1 The amount of acid can be determined by a method of calculating the result of H-NMR measurement; or by a method of determining the amount of acid by neutralization titration and calculating from the determined amount of acid.

[0086] The polymerization catalyst (graft polymerization catalyst) used for graft polymerization is not particularly limited, and examples thereof include inorganic peroxides such as sodium persulfate, potassium persulfate, ammonium persulfate, potassium perphosphate, and hydrogen peroxide; organic peroxides such as diisopropylbenzene hydroperoxide, cumene hydroperoxide, tert-butyl hydroperoxide, 1,1,3,3-tetramethylbutyl hydroperoxide, di-tert-butyl peroxide, isobutyryl peroxide, and benzoyl peroxide; azo compounds such as 2,2'-azobisisobutyronitrile, azobis-2,4-dimethylvaleronitrile, and methyl azobisisobutyrate, etc., preferably organic peroxides, and particularly preferably 1,1,3,3-tetramethylbutyl hydroperoxide.

[0087] The above-mentioned graft polymerization catalysts can be used alone or in combination of two or more. The amount of the graft polymerization catalyst used varies depending on its type, and is preferably 0.1 to 10 parts by weight, more preferably 0.2 to 5 parts by weight, relative to 100 parts by weight of the conjugated diene polymer. In addition, there is no particular limitation on the method of adding the graft polymerization catalyst, and known addition methods such as one-time addition, batch addition, and continuous addition can be used.

[0088] The conjugated diene polymer (including the conjugated diene polymer modified by a carboxyl group) used in the present invention preferably has a swelling index (SI) of 105 to 300%, more preferably 110 to 250%, and even more preferably 120 to 200%. By setting the swelling index (SI) within the above range, the reduction in mechanical strength of the film molded product of the present invention during high temperature storage can be further suppressed, and further, the tensile strength and tear strength of the film molded product of the present invention at room temperature can be improved.

[0089] The swelling index (SI) can be obtained by forming a latex of a conjugated diene polymer into a film, immersing the obtained conjugated diene polymer film in toluene at 25° C. for 1 hour, measuring the width of the film before and after the toluene immersion, and measuring the linear swelling ratio. Specifically, the swelling index (SI) can be obtained according to the following formula.

[0090] Swelling index (SI) [%] = [{(width of the film after toluene immersion) - (width of the film before toluene immersion)} / (width of the film before toluene immersion)] × 100

[0091] As a method for preparing a film for measuring the swelling index (SI) of a latex of a conjugated diene polymer, for example, the following immersion method can be adopted.

[0092] That is, in the dipping method, first, an acid or alkali is added to the latex of the conjugated diene polymer to adjust the pH to 8.2. Then, a ceramic molding die with a frosted surface is prepared, cleaned, and preheated in an oven at 70°C for 30 minutes, and then the preheated ceramic molding die is immersed in a coagulant aqueous solution containing 18% by weight of calcium nitrate and 0.05% by weight of polyoxyethylene lauryl ether (trade name "EMULGEN 109P", manufactured by Kao Corporation) for 5 seconds. Then, the ceramic molding die is taken out from the coagulant aqueous solution, and the ceramic molding die coated with the coagulant is dried in an oven at 70°C for 20 minutes. Next, the ceramic forming mold coated with the coagulant is taken out of the oven, and the ceramic forming mold taken out is immersed in the latex of the conjugated diene polymer adjusted to pH=8.2 under the conditions of 25°C and 10 seconds, and then taken out, and the ceramic forming mold coated with the latex of the conjugated diene polymer is immersed in warm water at 60°C for 2 minutes, and then dried at room temperature for 6 hours to obtain a ceramic forming mold coated with a film for measurement. Then, after talc is scattered therein, the film for measurement is peeled off from the ceramic forming mold, thereby obtaining a film for measurement. In addition, the thickness of the film for measurement is not particularly limited, and is preferably about 0.2 mm.

[0093] In addition, as a method for adjusting the swelling index (SI) of the latex of the conjugated diene polymer to the above range, it is not particularly limited, and for example, a method for adjusting the type and composition of the conjugated diene polymer can be cited. Wherein, as a conjugated diene polymer, in the case of using a carboxyl-modified conjugated diene polymer, it can be cited: a method for adjusting the reaction temperature (modification reaction temperature) and the reaction time (modification reaction time) when the conjugated diene polymer reacts with a monomer having a carboxyl group; a method for selecting whether to post-heat the latex after the reaction; a method for adjusting the post-heating temperature and the post-heating time when the latex after the reaction is post-heated; a method for adjusting the type and amount of the monomer having a carboxyl group used in the modification reaction; and a method for adjusting the type and amount of the reducing agent used in combination with an organic peroxide in the modification reaction, etc., preferably, they are appropriately combined for adjustment.

[0094] The latex of the conjugated diene polymer (including the carboxyl-modified conjugated diene polymer) used in the present invention may contain additives such as pH adjusters, defoamers, preservatives, chelating agents, deoxidizers, and dispersants commonly used in the latex field.

[0095] Examples of the pH adjuster include alkali metal hydroxides such as sodium hydroxide and potassium hydroxide; alkali metal carbonates such as sodium carbonate and potassium carbonate; alkali metal hydrogen carbonates such as sodium hydrogen carbonate; ammonia; and organic amine compounds such as trimethylamine and triethanolamine. Alkali metal hydroxides or ammonia are preferred.

[0096] The solid content concentration of the latex of the conjugated diene polymer (including the conjugated diene polymer modified by a carboxyl group) used in the present invention is preferably 30 to 70% by weight, more preferably 40 to 70% by weight. By making the solid content concentration within the above range, the generation of coagulation in the latex can be more effectively suppressed, and the separation of polymer particles during storage of the latex can be more effectively suppressed.

[0097] The latex composition used in the present invention contains a sulfur-based vulcanizing agent.

[0098] The sulfur-based vulcanizing agent is not particularly limited, and examples thereof include sulfur such as powdered sulfur, sublimated sulfur, precipitated sulfur, colloidal sulfur, surface-treated sulfur, and insoluble sulfur; sulfur compounds such as sulfur chloride, sulfur dichloride, morpholine disulfide, alkylphenol disulfide, caprolactam disulfide (N,N'-dithiobis(hexahydro-2H-azepinone-2)), phosphorus-containing polysulfide, polymer polysulfide, and 2-(4'-morpholinodithio)benzothiazole. Of these, sulfur can be preferably used. The sulfur-based vulcanizing agent can be used alone or in combination of two or more.

[0099] The content of the sulfur-based vulcanizing agent in the latex composition is not particularly limited, but is preferably 0.01 to 3 parts by weight, more preferably 0.1 to 1.2 parts by weight, further preferably 0.1 to 0.8 parts by weight, further preferably 0.1 to 0.6 parts by weight, and particularly preferably 0.2 to 0.6 parts by weight, relative to 100 parts by weight of the conjugated diene polymer contained in the latex composition. By making the content of the sulfur-based vulcanizing agent within the above range, the occurrence of delayed hypersensitivity (IV type) symptoms can be suppressed in the obtained dip molded article, and the tensile strength and tear strength at room temperature can be improved.

[0100] The latex composition used in the present invention contains a vulcanization accelerator. As the vulcanization accelerator, a xanthogenic acid compound is preferably used from the viewpoint of suppressing the occurrence of delayed hypersensitivity (type IV) symptoms in the obtained dip-molded article.

[0101] The xanthogenic acid compound is not particularly limited, and examples thereof include xanthogenic acid, xanthogenic acid salts, xanthogenic acid disulfides (compounds in which two xanthogenic acids are bonded via a sulfur atom or the like), and xanthogenic acid polysulfides (compounds in which three or more xanthogenic acids are bonded via a sulfur atom or the like).

[0102] Xanthate salts are not particularly limited as long as they have a xanthate structure, and examples thereof include compounds represented by the general formula (ROC(=S)S)xZ (wherein R is a linear or branched hydrocarbon, and Z is a metal atom. x is a number consistent with the valence of Z, and is usually 1 to 4, preferably 2 to 4, and particularly preferably 2).

[0103] The xanthate represented by the general formula (ROC(=S)S)xZ is not particularly limited, and examples thereof include dimethyl zinc xanthate, diethyl zinc xanthate, dipropyl zinc xanthate, diisopropyl zinc xanthate, dibutyl zinc xanthate, diamyl zinc xanthate, dihexyl zinc xanthate, diheptyl zinc xanthate, dioctyl zinc xanthate, di(2-ethylhexyl) zinc xanthate, didecyl zinc xanthate, didodecyl zinc xanthate, dimethyl potassium xanthate, ethyl potassium xanthate, propyl xanthate, Xanthate, potassium isopropyl xanthate, potassium butyl xanthate, potassium amyl xanthate, potassium hexyl xanthate, potassium heptyl xanthate, potassium octyl xanthate, potassium 2-ethylhexyl xanthate, potassium decyl xanthate, potassium dodecyl xanthate, sodium methyl xanthate, sodium ethyl xanthate, sodium propyl xanthate, sodium isopropyl xanthate, sodium butyl xanthate, sodium amyl xanthate, sodium hexyl xanthate, sodium heptyl xanthate, sodium octyl xanthate, sodium 2-ethylhexyl xanthate, sodium decyl xanthate, sodium dodecyl xanthate, etc. Among these, xanthate in the general formula (ROC(=S)S)xZ in which x is 2 or more is preferred, isopropyl xanthate and butyl xanthate are more preferred, and diisopropyl zinc xanthate and dibutyl zinc xanthate are particularly preferred. These xanthates may be used alone or in combination of two or more.

[0104] The xanthate disulfide is a compound in which two xanthate acids are bonded via a sulfur atom or the like. It is not particularly limited, and examples thereof include dimethyl xanthate disulfide, diethyl xanthate disulfide, diisopropyl xanthate disulfide, dibutyl xanthate disulfide, dimethyl xanthate polysulfide, diethyl xanthate polysulfide, diisopropyl xanthate polysulfide, and dibutyl xanthate polysulfide. Among these, diisopropyl xanthate disulfide and dibutyl xanthate disulfide are preferred.

[0105] Xanthogenic acid polysulfide is a compound in which three or more xanthogenic acids are bonded via a sulfur atom or the like, and examples thereof include xanthogenic acid trisulfide in which three xanthogenic acids are bonded via sulfur, xanthogenic acid tetrasulfide in which four xanthogenic acids are bonded via sulfur, and xanthogenic acid pentasulfide in which five xanthogenic acids are bonded via sulfur.

[0106] In addition, these xanthate compounds may be contained in the latex composition alone, or preferably in two or more forms. For example, when xanthate is added to the latex composition, a portion of the added xanthate exists in the form of a xanthate, and as a result, two or more xanthate compounds may be contained in the latex composition. Alternatively, a portion of the xanthate added to the latex composition may exist in the form of a xanthate disulfide or a xanthate polysulfide due to the action of a sulfur-based vulcanizing agent in the latex composition. Similarly, when a xanthate, a xanthate disulfide or a xanthate polysulfide is added to the latex composition, they may exist in the form of any one of xanthate, a xanthate, a xanthate disulfide or a xanthate polysulfide, respectively.

[0107] Furthermore, in the present invention, as the vulcanization accelerator, a vulcanization accelerator other than the xanthogenic acid compound may be used instead of the xanthogenic acid compound or together with the xanthogenic acid compound.

[0108] As such a vulcanization accelerator other than the xanthate compound, a vulcanization accelerator commonly used in dip molding can be used, for example: dithiocarbamic acids such as diethyldithiocarbamic acid, dibutyldithiocarbamic acid, di-2-ethylhexyldithiocarbamic acid, dicyclohexyldithiocarbamic acid, diphenyldithiocarbamic acid, dibenzyldithiocarbamic acid and their zinc salts; 2-mercaptobenzothiazole, 2-mercaptobenzothiazole, Zinc benzothiazole, 2-mercaptothiazoline, dibenzothiazole disulfide, 2-(2,4-dinitrophenylthio)benzothiazole, 2-(N,N-diethylthiocarbamoylthio)benzothiazole, 2-(2,6-dimethyl-4-morpholinylthio)benzothiazole, 2-(4'-morpholinyldithio)benzothiazole, 4-morpholinyl-2-benzothiazole disulfide, 1,3-bis(2-benzothiazolylmercaptomethyl)urea, etc. The vulcanization accelerator can be used alone or in combination of two or more.

[0109] The content of the vulcanization accelerator in the latex composition (the total content when a plurality of vulcanization accelerators are included) is preferably 0.01 to 10 parts by weight, more preferably 0.1 to 7 parts by weight, and even more preferably 0.5 to 5 parts by weight relative to 100 parts by weight of the conjugated diene polymer included in the latex composition. By making the content of the vulcanization accelerator within the above range, the reduction in mechanical strength of the film molded product of the present invention when stored at high temperature can be further suppressed, and the tensile strength and tear strength of the film molded product of the present invention at room temperature can also be improved.

[0110] Furthermore, when the latex composition used in the present invention contains a xanthogenic acid compound as a vulcanization accelerator, the latex composition used in the present invention may further contain an activator.

[0111] When a film formed body obtained from a latex composition containing an activator is cross-linked, the activator acts as a vulcanization accelerator together with the above-mentioned xanthogenic acid compound, thereby further suppressing the decrease in tear strength of the cross-linked film formed body when the cross-linked film formed body is stored at high temperature, and also improving the tear strength of the cross-linked film formed body at room temperature.

[0112] As an activator, it is not particularly limited. From the viewpoint of further improving the tear strength of the film forming body, it is preferred to use a metal compound. As a metal compound, it is not particularly limited, and examples thereof include metal oxides, metal compounds containing at least one carbon atom, etc. As the metal constituting the metal compound, it is not particularly limited, and typical metals (selected from at least one element of the 1st group element, the 2nd group element, the 12th group element, the 13th group element, the 14th group element, the 15th group element, the 16th group element, the 17th group element, and the 18th group element) are preferred, and it is more preferred to select from the 2nd group element, the 12th group element, the 13th group element, and the 14th group element, and further preferably zinc, magnesium, calcium, aluminum, and lead, and particularly preferably zinc, magnesium, and calcium, and most preferably zinc. These metal compounds can be used alone or in combination.

[0113] The metal oxide is not particularly limited, but from the viewpoint of further improving the tear strength of the obtained dip-molded body, zinc oxide, magnesium oxide, titanium oxide, calcium oxide, lead oxide, iron oxide, copper oxide, tin oxide, nickel oxide, chromium oxide, cobalt oxide and aluminum oxide are preferred, and zinc oxide is more preferred.

[0114] As the metal compound containing at least one carbon atom, carbonates, bicarbonates, hydroxides, and organometallic compounds are preferred from the viewpoint of further improving the tear strength of the obtained impregnated molded body, and carbonates, bicarbonates, and organometallic compounds are more preferred. Among these, inorganic salts such as carbonates and bicarbonates are particularly preferred from the viewpoint of excellent stability of the compound itself and excellent ease of acquisition.

[0115] The content of the activator in the latex composition is preferably 0.01 to 10 parts by weight, more preferably 0.1 to 5 parts by weight, and even more preferably 1 to 3 parts by weight, relative to 100 parts by weight of the conjugated diene polymer contained in the latex composition. By making the content of the activator within the above range, the decrease in the tear strength of the film molded product of the present invention when stored at high temperature can be further suppressed, and the tear strength of the film molded product of the present invention at room temperature can also be improved.

[0116] The method for blending the activator is not particularly limited as long as it is a method that ultimately results in a state where the latex of the conjugated diene polymer and the activator are mixed.

[0117] The latex composition used in the present invention contains as an antioxidant at least one selected from phenolic antioxidants and quinoline antioxidants and having a molecular weight of 300 to 600 (hereinafter sometimes referred to as "specific antioxidant").

[0118] In the present specification, the phenolic antioxidant is an aromatic compound having one or more phenolic hydroxyl groups (hydroxyl groups directly bonded to the benzene ring structure in the aromatic compound).

[0119] As a phenolic antioxidant used as a specific antioxidant, an aromatic compound having a hindered phenol structure is preferred. In addition, in the present specification, a hindered phenol structure means a structure in which one of the two ortho positions of a phenolic hydroxyl group is substituted by a hydrocarbon group having 4 or more carbon atoms and the other is substituted by a substituent other than a hydrogen atom. In addition, the above-mentioned hydrocarbon group having 4 or more carbon atoms located at an ortho position of a phenolic hydroxyl group may have a substituent. As an aromatic compound having a hindered phenol structure, an aromatic compound having a structure in which one of the two ortho positions of a phenolic hydroxyl group is substituted by a tert-butyl group and the other is substituted by a substituent other than a hydrogen atom is preferred.

[0120] As a phenolic antioxidant, a specific antioxidant, it is sufficient as long as it has at least one phenolic hydroxyl group and a molecular weight in the range of 300 to 600. For example, in the present invention, it can be classified into an aromatic compound (a) having two or more phenolic hydroxyl groups and an aromatic compound (b) having one phenolic hydroxyl group. In addition, in the present specification, "a compound having two or more phenolic hydroxyl groups" includes a compound having one or more benzene ring structures bonded to two or more phenolic hydroxyl groups, and a compound having two or more benzene ring structures bonded to one or more phenolic hydroxyl groups. That is, the two or more phenolic hydroxyl groups present in the aromatic compound (a) having two or more phenolic hydroxyl groups can be bonded to the same benzene ring or to different benzene rings.

[0121] Examples of the aromatic compound (a) having two or more phenolic hydroxyl groups include 2,2'-methylenebis(4-methyl-6-tert-butylphenol), 2,2'-methylenebis(4-ethyl-6-tert-butylphenol), 4,4'-methylenebis(2,6-di-tert-butylphenol), 2,2'-methylene-bis(6-α-methyl-benzyl-p-cresol), 4,4'-butylenebis(3-methyl-6-tert-butylphenol), 4,4'-thiobis(6-tert-butyl-o-cresol), 2,2'-thiobis-(4-methyl-6-tert-butylphenol), 4,4'-thiobis(3-methyl-6-tert-butylphenol), [ethylenebis(oxyethylene)]bis[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate], and the like. The molecular weight of the aromatic compound (a) having two or more phenolic hydroxyl groups is preferably 310 to 590, more preferably 320 to 540, and even more preferably 330 to 440.

[0122] As the aromatic compound (a) having two or more phenolic hydroxyl groups, an aromatic compound (a-1) having two or more hindered phenol structures is preferred from the viewpoint of being able to further suppress a decrease in the mechanical strength of the obtained film molding during storage at high temperatures. Examples of the aromatic compound (a-1) having two or more hindered phenol structures include 2,2'-methylenebis(4-methyl-6-tert-butylphenol), 2,2'-methylenebis(4-ethyl-6-tert-butylphenol), 4,4'-methylenebis(2,6-di-tert-butylphenol), 2,2'-methylene-bis(6-α-methyl-benzyl-p-cresol), 4,4'-thiobis(6-tert-butyl-o-cresol), 2,2'-thiobis-(4-methyl-6-tert-butylphenol), [ethylenebis(oxyethylene)]bis[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate], and the like.

[0123] As the aromatic compound (a-1) having two or more hindered phenol structures, an aromatic compound (a-2) having a diphenylmethane skeleton and having two or more hindered phenol structures and having a molecular weight of 300 to 600 is more preferred. As the aromatic compound (a-2) having a diphenylmethane skeleton and having two or more hindered phenol structures, for example, 2,2'-methylenebis(4-methyl-6-tert-butylphenol), 2,2'-methylenebis(4-ethyl-6-tert-butylphenol), 4,4'-methylenebis(2,6-di-tert-butylphenol), 2,2'-methylene-bis(6-α-methyl-benzyl-p-cresol) and the like can be cited. Among the aromatic compounds (a-2) having a diphenylmethane skeleton and having two or more hindered phenol structures, aromatic compounds (a-3) in which the two benzene rings constituting the diphenylmethane skeleton each have a hindered phenol structure are preferred, among which 4,4'-methylenebis(2,6-di-tert-butylphenol) or 2,2'-methylenebis(4-methyl-6-tert-butylphenol) is more preferred, and 2,2'-methylenebis(4-methyl-6-tert-butylphenol) is further preferred.

[0124] Examples of the aromatic compound (b) having one phenolic hydroxyl group include 2,6-di-tert-butyl-4-(4,6-bis(octylthio)-1,3,5-triazin-2-ylamino)phenol, octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, octyl-3,5-di-tert-butyl-4-hydroxy-hydrocinnamate, and 4,6-bis[(dodecylthio)methyl]-6-methylphenol. The molecular weight of the aromatic compound (b) having one phenolic hydroxyl group is preferably 350 to 600, more preferably 400 to 600, and even more preferably 450 to 600.

[0125] As the aromatic compound (b) having one phenolic hydroxyl group, an aromatic compound (b-1) having one phenolic hydroxyl group and one or more -NH- bonds is preferred. The aromatic compound (b-1) having one phenolic hydroxyl group and one or more -NH- bonds can make the obtained film-formed body have excellent resistance to ozone degradation. As the aromatic compound (b-1) having one phenolic hydroxyl group and one or more -NH- bonds, 2,6-di-tert-butyl-4-(4,6-bis(octylthio)-1,3,5-triazine-2-ylamino)phenol is preferred.

[0126] The quinoline antioxidant may be any heterocyclic aromatic compound (quinoline which may have a substituent) having one or more quinoline structures and having a molecular weight in the range of 300 to 600. Examples of the quinoline antioxidant include 2,2,4-trimethyl-1,2-dihydroquinoline polymers.

[0127] As the specific antioxidant used in the present invention, it is preferred to contain at least a phenolic antioxidant, more preferably at least an aromatic compound (a) having two or more phenolic hydroxyl groups, further preferably an aromatic compound (a) having two or more phenolic hydroxyl groups and an aromatic compound (b) having one phenolic hydroxyl group, particularly preferably an aromatic compound (a) having two or more phenolic hydroxyl groups and an aromatic compound (b-1) having one phenolic hydroxyl group and one or more -NH- bonds, particularly preferably an aromatic compound (a-1) having two or more hindered phenol structures and an aromatic compound (b-1) having one phenolic hydroxyl group and one or more -NH- bonds, and most preferably an aromatic compound (a-2) having a diphenylmethane skeleton with two or more hindered phenol structures and an aromatic compound (b-1) having one phenolic hydroxyl group and one or more -NH- bonds.

[0128] In the case where the specific antioxidant used in the present invention comprises an aromatic compound (a) having two or more phenolic hydroxyl groups and an aromatic compound (b) having one phenolic hydroxyl group, the weight-based content ratio of the aromatic compound (a) having two or more phenolic hydroxyl groups to the aromatic compound (b) having one phenolic hydroxyl group (aromatic compound (a) having two or more phenolic hydroxyl groups: aromatic compound (b) having one phenolic hydroxyl group) is preferably 1:99 to 99:1, more preferably 10:90 to 98:2, more preferably 25:75 to 95:5, and particularly preferably 55:45 to 90:10.

[0129] The molecular weight of the specific antioxidant used in the present invention is not particularly limited as long as it is 300 to 600. In addition, as the specific antioxidant, two or more specific antioxidants can be used in combination. When the latex composition contains two or more specific antioxidants, the weight average molecular weight of the two or more specific antioxidants is used as the molecular weight of the specific antioxidant. That is, in the present invention, the weight average molecular weight of the specific antioxidant contained in the latex composition is 300 to 600. The molecular weight of the specific antioxidant used in the present invention is preferably 310 to 590, more preferably 320 to 540, and even more preferably 330 to 440 from the aspect of being able to further suppress the reduction of the mechanical strength of the film molding of the present invention when stored at high temperature.

[0130] The content of the specific antioxidant in the latex composition is preferably 0.05 to 10 parts by weight, more preferably 0.1 to 5 parts by weight, and even more preferably 0.5 to 3 parts by weight, based on 100 parts by weight of the conjugated diene polymer contained in the latex composition.

[0131] The latex composition used in the present invention may contain an antioxidant other than the above-mentioned specific antioxidant, but preferably contains no antioxidant other than the above-mentioned specific antioxidant.

[0132] The latex composition may further contain various compounding agents such as a dispersant, a reinforcing agent such as carbon black, silica, and talc, a filler such as calcium carbonate and clay, an ultraviolet absorber, and a plasticizer as required.

[0133] The method of mixing various compounding ingredients in the latex composition is not particularly limited, and examples thereof include a method of mixing various compounding ingredients as required with a composition containing a latex of a conjugated diene polymer, a sulfur-based vulcanizing agent, a vulcanization accelerator, and the above-mentioned specific antioxidant using a dispersing machine such as a ball mill, a kneader, or a disperser, etc. In addition, at least a part of the various compounding ingredients may be mixed after aging as described below.

[0134] The solid content concentration of the latex composition used in the present invention is preferably 1 to 40% by weight, more preferably 3 to 35% by weight, further preferably 5 to 30% by weight, and particularly preferably 10 to 20% by weight. By making the solid content concentration of the latex composition within the above range, the coagulation stability of the latex can be highly maintained, and even when the obtained film molding is made as thin as 20 to 300 μm, the reduction in mechanical strength of the film molding when stored at high temperature can be further suppressed, and the tensile strength and tear strength at room temperature can also be excellent.

[0135] In addition, the latex composition used in the present invention is preferably aged (pre-vulcanized) before molding from the viewpoint of ensuring that the mechanical properties of the obtained film molding are sufficient. The aging (pre-vulcanization) time is not particularly limited, and is preferably 8 to 120 hours, and more preferably 24 to 72 hours. The aging (pre-vulcanization) temperature is not particularly limited, and is preferably 20 to 40°C. In addition, when using the above-mentioned latex composition, after aging (pre-vulcanization) for a specified time, it is also possible to continuously perform molding such as dip molding while maintaining the aging (pre-vulcanization) conditions (while continuing aging (pre-vulcanization)), and the aging (pre-vulcanization) time and aging (pre-vulcanization) temperature at this time can be set within the above-mentioned range.

[0136] <Film molding>

[0137] The film-molded product of the present invention is a film-molded product having a thickness of 20 to 300 μm obtained by using the above-mentioned latex composition.

[0138] The thickness of the film molded body of the present invention may be 20 to 300 μm, but is not particularly limited, and is preferably 50 to 280 μm, more preferably 100 to 260 μm, and particularly preferably 140 to 250 μm. The thickness of the film molded body can be obtained by, for example, selecting 5 measurement locations from the film molded body, measuring the thickness of the selected 5 locations, and calculating the arithmetic average thereof.

[0139] The film-molded body of the present invention is not particularly limited, but preferably is a dip-molded body obtained by dip-molding the above-mentioned latex composition. Dip molding is a method of dipping a mold in a latex composition, depositing the composition on the surface of the mold, then lifting the mold from the composition, and then drying the composition deposited on the surface of the mold. In addition, the mold before dipping in the latex composition can be preheated in advance. In addition, before dipping the mold in the latex composition or after lifting the mold from the latex composition, a coagulant can be used as needed.

[0140] Specific examples of methods for using a coagulant include a method in which a mold before being immersed in a latex composition is immersed in a solution of the coagulant and the coagulant is attached to the mold (anodic coagulation dipping method); a method in which a mold on which a latex composition is deposited is immersed in a coagulant solution (Teague coagulation dipping method), etc. From the viewpoint of obtaining an impregnated molded body with less uneven thickness, the anodic coagulation dipping method is preferred.

[0141] Specific examples of the coagulant include metal halides such as barium chloride, calcium chloride, magnesium chloride, zinc chloride, and aluminum chloride; nitrates such as barium nitrate, calcium nitrate, and zinc nitrate; acetates such as barium acetate, calcium acetate, and zinc acetate; and sulfates such as calcium sulfate, magnesium sulfate, and aluminum sulfate. Among them, calcium salts are preferred, and calcium nitrate is more preferred. These water-soluble multivalent metal salts can be used alone or in combination of two or more.

[0142] The coagulant can be used in the form of an aqueous solution, an alcohol solution, or a mixture thereof, preferably in the form of an aqueous solution. The aqueous solution may also contain a water-soluble organic solvent such as methanol or ethanol, or a nonionic surfactant. The concentration of the coagulant varies depending on the type of the water-soluble multivalent metal salt, but is preferably 5 to 50% by weight, more preferably 10 to 30% by weight.

[0143] After the mold is lifted from the latex composition, the deposit formed on the mold is usually dried by heating. The drying conditions can be appropriately selected.

[0144] The obtained dip-molded layer is preferably subjected to a heat treatment for cross-linking.

[0145] Before the heat treatment, the obtained dip-molded layer may be immersed in water, preferably warm water at 30 to 70° C., for about 1 to 60 minutes to remove water-soluble impurities (e.g., excess emulsifier, coagulant, etc.). The removal of water-soluble impurities may be performed after the dip-molded layer is heat-treated, but is preferably performed before the heat treatment from the viewpoint of being able to more efficiently remove water-soluble impurities.

[0146] The crosslinking of the dip molded layer is usually performed by heating at a temperature of 80 to 150° C., preferably for 10 to 130 minutes. As the heating method, external heating using infrared rays or heated air or internal heating using high frequency waves can be used. Among them, external heating using heated air is preferred.

[0147] Then, the dip-molded layer is separated from the dip-molding die to obtain a dip-molded body in the form of a film-shaped film-molded body. As a separation method, it is possible to adopt a method of peeling off from the molding die by hand, or peeling off by water pressure or compressed air pressure. In addition, after the separation, it is also possible to further perform a heat treatment at a temperature of 60 to 120° C. for 10 to 120 minutes.

[0148] The film-molded product of the present invention can be obtained by any method other than the method of dipping the latex composition as long as the latex composition can be molded into a film (for example, a coating method).

[0149] The film molded body of the present invention is suppressed from decreasing in mechanical strength when stored at high temperature. Therefore, the film molded body of the present invention can be preferably used as an article that requires mechanical properties such as tensile strength and tear strength and can be stored at a high temperature of about 70°C or less, or an article that can be stored at room temperature for a long time. For example, the film molded body of the present invention can be particularly preferably used as a glove. In the case where the film molded body is a glove, in order to prevent the contact surfaces of the film molded bodies from being closely attached and to improve the sliding when putting on and taking off, inorganic particles such as talc and calcium carbonate or organic particles such as starch particles can be scattered on the surface of the glove, an elastic layer containing particles can be formed on the surface of the glove, and the surface layer of the glove can be chlorinated.

[0150] In addition, the film-formed body of the present invention can be used not only for the above-mentioned gloves, but also for medical supplies such as pacifiers for baby bottles, droppers, tubes, water pillows, inflatable air bags, catheters, condoms, etc.; toys such as balloons, dolls, balls, etc.; industrial products such as bags for pressure molding and gas storage bags; finger cots, etc.

[0151] Example

[0152] Hereinafter, the present invention will be described in detail by way of examples, but the present invention is not limited to these examples. In addition, unless otherwise specified, the following "parts" are weight references. In addition, various physical properties are measured as follows.

[0153] <Solid content concentration>

[0154] 2 g of the sample (weight: X2) was accurately weighed in an aluminum pan (weight: X1) and dried in a hot air dryer at 105°C for 2 hours. After cooling in the dryer, the weight of the sample including the aluminum pan (weight: X3) was measured and the solid content concentration was calculated according to the following calculation formula.

[0155] Solid content concentration (weight %) = (X3-X1) × 100 / X2

[0156] <Modification Rate of Carboxyl-Modified Synthetic Polyisoprene>

[0157] The number of carboxyl groups in the carboxyl-modified synthetic polyisoprene constituting the latex of the carboxyl-modified synthetic polyisoprene was determined by neutralization titration using an aqueous sodium hydroxide solution. Next, based on the determined number of carboxyl groups, the modification rate of the monomer having a carboxyl group was determined according to the following formula.

[0158] Modification rate (weight %) = (X / Y) × 100

[0159] In the above formula, X represents the weight of the unit of the monomer having a carboxyl group in the carboxyl group-modified synthetic polyisoprene, and Y represents the weight of the carboxyl group-modified synthetic polyisoprene.

[0160] <Swelling Index (SI)>

[0161] Potassium hydroxide was added to the latex of carboxyl-modified synthetic polyisoprene to adjust the pH to 8.2. Then, a ceramic molding die with a frosted surface was prepared, cleaned, and preheated in an oven at 70°C for 60 minutes. The preheated ceramic molding die was immersed in a coagulant aqueous solution containing 18% by weight of calcium nitrate and 0.05% by weight of polyoxyethylene lauryl ether (trade name "EMULGEN 109P", manufactured by Kao Corporation) for 5 seconds. Then, the ceramic molding die was taken out of the coagulant aqueous solution, and the ceramic molding die coated with the coagulant was dried in an oven at 70°C for 20 minutes. Next, the ceramic forming mold coated with the coagulant is taken out of the oven, and the taken out ceramic forming mold is immersed in a latex of carboxyl-modified synthetic polyisoprene adjusted to pH = 8.2 under the conditions of 25°C and 10 seconds, and then taken out, and the ceramic forming mold coated with the latex of carboxyl-modified synthetic polyisoprene is immersed in warm water at 60°C for 2 minutes, and then dried at room temperature for 6 hours, thereby obtaining a ceramic forming mold coated with a film for measurement. Then, after talc is spread therein, the obtained film is peeled off from the ceramic forming mold, thereby obtaining an impregnated film with a thickness of 0.2 mm. Then, a test film with a diameter of 25 mm is cut out from the obtained impregnated film, and the obtained test film is immersed in toluene at 25°C for 1 hour, and the width of the test piece before and after toluene immersion is measured, and the swelling index (SI) is calculated according to the following formula.

[0162] Swelling index (SI) [%] = [{(width of the film after toluene immersion) - (width of the film before toluene immersion)} / (width of the film before toluene immersion)] × 100

[0163] <Thickness of Impregnated Molded Body>

[0164] When the glass mold is immersed in the coagulant solution, five measurement sites are selected within 3 cm of the site of the dip-molded body corresponding to the site (the front end of the glass mold) where the contact time with the coagulant solution is the longest. Then, the thickness of the selected five sites is measured, and the arithmetic average of the thicknesses of the five measured sites is calculated, and the obtained value (unit: mm) is used as the thickness of the dip-molded body.

[0165] <Tensile strength of dip molded article>

[0166] The impregnated body (impregnated body before aging) was heated at 70°C for 7 days to obtain an impregnated body after aging. Based on ASTM D412, the impregnated body before aging and the impregnated body after aging were punched out with a dumbbell cutter (trade name "Super Dumbbell (model: SDMK-100C)", manufactured by DUMBBELL Co., Ltd.) to prepare a test piece for tensile strength measurement. The test piece was stretched at a tensile speed of 500 mm / min using a Tensilon universal testing machine (trade name "RTG-1210", manufactured by Orientec Co., Ltd.), and the tensile strength (unit: MPa) at the time of breaking was measured.

[0167] <Tear strength of dip molded article>

[0168] The aged impregnated body (impregnated body before aging) was heated at 70°C for 7 days to obtain an aged impregnated body. Based on ASTM D624-00, the impregnated body before aging and the impregnated body after aging were placed in a constant temperature and humidity chamber at 23°C and a relative humidity of 50% for more than 24 hours, and then punched out with a dumbbell cutter (trade name "Die C", manufactured by DUMBBELL Co., Ltd.) to prepare a test piece for tear strength measurement. The test piece was stretched at a tensile speed of 500 mm / min using a Tensilon universal testing machine (trade name "RTG-1210", manufactured by A&D Co., Ltd.) to measure the tear strength (unit: N / mm).

[0169] <Production Example 1>

[0170] (Production of Latex (A-1) of Carboxyl-Modified Synthetic Polyisoprene)

[0171] Synthetic polyisoprene (trade name "NIPOL IR2200L", manufactured by Nippon Zeon Co., Ltd.) was mixed with n-hexane (boiling point: 69°C) and dissolved by heating to 60°C while stirring to prepare an n-hexane solution (a) of synthetic polyisoprene having a synthetic polyisoprene concentration of 15 wt%.

[0172] On the other hand, potassium rosinate was added to water and dissolved by heating the water to 60°C to prepare an emulsifier aqueous solution (b) having a concentration of 1.5% by weight.

[0173] Next, the n-hexane solution of synthetic polyisoprene (a) and the aqueous emulsifier solution (b) obtained above were mixed using a mixer (product name "Multi Line Mixer MS26-MMR-5.5L", manufactured by Satake Chemical Machinery Co., Ltd.) so that the potassium rosinate in the aqueous emulsifier solution (b) was 10 parts per 100 parts of synthetic polyisoprene in the n-hexane solution of synthetic polyisoprene (a), and then mixed and emulsified at a rotation speed of 4100 rpm using an emulsifier (product name "Milder MDN310", manufactured by Pacific Machinery Co., Ltd.), thereby obtaining an emulsified dispersion (c). In this case, the total feed flow rate of the n-hexane solution of synthetic polyisoprene (a) and the aqueous emulsifier solution (b) was 2000 kg / hour, the temperature was 60°C, and the back pressure (gauge pressure) was 0.5 MPa.

[0174] Next, the obtained emulsified dispersion (c) was heated to 80°C under a reduced pressure of -0.01 to -0.09 MPa (gauge pressure), and the n-hexane was distilled off to obtain an aqueous dispersion (d) of synthetic polyisoprene. At this time, a defoamer (trade name "SM5515", manufactured by Dow Corning Toray Industries, Ltd.) was continuously added while spraying in an amount of 300 ppm by weight relative to the synthetic polyisoprene in the emulsified dispersion (c). In addition, when the n-hexane was distilled off, the emulsified dispersion (c) was adjusted to less than 70% by volume of the tank volume, and a three-stage inclined paddle blade was used as a stirring blade, and stirring was slowly performed at 60 rpm.

[0175] After the distillation of n-hexane was completed, the obtained aqueous dispersion of synthetic polyisoprene (d) was centrifuged at 8000 to 9000 G using a continuous centrifuge (product name "SRG510", manufactured by Alfa Laval) to concentrate the aqueous dispersion, thereby obtaining a latex of synthetic polyisoprene (e) having a solid content concentration of 60% by weight as a light liquid. The conditions for the centrifugation were as follows: the solid content concentration of the aqueous dispersion (d) before the centrifugation was 8% by weight, the flow rate during the continuous centrifugation was 1300 kg / hour, and the back pressure (gauge pressure) of the centrifuge was 0.1 MPa.

[0176] Next, 130 parts of distilled water were added to 100 parts of the obtained synthetic polyisoprene latex (e) for dilution. Then, 0.8 parts of sodium salt of β-naphthalenesulfonic acid formaldehyde condensate (trade name "Demol T-45", manufactured by Kao Corporation) as a dispersant was diluted with 4 parts of distilled water relative to 100 parts of the synthetic polyisoprene, and the obtained product was added to the latex (e) of synthetic polyisoprene over 5 minutes. Next, the latex (e) of synthetic polyisoprene to which the dispersant was added was added to a nitrogen-substituted reaction vessel with a stirrer, and the temperature was heated to 30°C while stirring. In addition, using another container, 3 parts of methacrylic acid as a carboxyl-containing compound and 16 parts of distilled water were mixed to prepare a methacrylic acid dilution. The methacrylic acid dilution was added to the reaction vessel maintained at 20°C over 30 minutes.

[0177] Furthermore, using another container, a solution (f) consisting of 7 parts of distilled water, 0.30 parts of sodium formaldehyde sulfoxylate (trade name "SFS", manufactured by Mitsubishi Gas Chemical Co., Ltd.), and 0.01 parts of ferrous sulfate (trade name "Frost Fe", manufactured by Chubu Gillister Co., Ltd.) was prepared. After the solution (f) was transferred to the reaction container, 0.5 parts of 1,1,3,3-tetramethylbutyl hydroperoxide (trade name "PEROCT H", manufactured by NOF Corporation) was added, and the mixture was reacted at 30°C for 1 hour to obtain a latex after the modification reaction. After the obtained latex after the modification reaction was further reacted at 40°C for 1 hour, it was concentrated using a centrifuge to obtain a latex (A-1) of carboxyl-modified synthetic polyisoprene having a solid content concentration of 60% by weight. The modification rate of the obtained latex (A-1) of carboxyl-modified synthetic polyisoprene was measured according to the above method, and the modification rate was 0.5 mol%. The swelling index (SI) of the obtained carboxyl-modified synthetic polyisoprene latex (A-1) was measured according to the above method. The swelling index (SI) of the carboxyl-modified synthetic polyisoprene in the carboxyl-modified synthetic polyisoprene latex (A-1) was 125%. The results are shown in Table 1 as the results of Examples 1 to 3, 5 and Comparative Examples 1 to 4.

[0178] <Production Example 2>

[0179] (Production of Latex (A-2) of Carboxyl-Modified Synthetic Polyisoprene)

[0180] The same method as in Manufacturing Example 1 was used to obtain a latex (e) of synthetic polyisoprene, and then, when performing a modification reaction using methacrylic acid, the amount of 1,1,3,3-tetramethylbutyl hydroperoxide (trade name "PEROCT H", manufactured by NOF Corporation) was changed from 0.5 parts to 0.3 parts to obtain a latex after the modification reaction. The latex after the modification reaction was further reacted at 40° C. for 1 hour, and then concentrated using a centrifuge to obtain a latex (A-2) of carboxyl-modified synthetic polyisoprene having a solid content concentration of 60% by weight. The modification rate of the obtained carboxyl-modified synthetic polyisoprene latex (A-2) was measured according to the above method, and the modification rate was 0.5 mol%. The swelling index (SI) was measured using the obtained carboxyl-modified synthetic polyisoprene latex (A-2) according to the above method. The swelling index (SI) of the carboxyl-modified synthetic polyisoprene in the latex (A-2) of the carboxyl-modified synthetic polyisoprene was 180%.

[0181] <Example 1>

[0182] (Preparation of Sulfur Aqueous Dispersion)

[0183] 0.5 parts of sulfur, 0.03 parts (6.0 parts per 100 parts of sulfur) of sodium salt of β-naphthalenesulfonic acid formaldehyde condensate (trade name "Demol T-45", manufactured by Kao Corporation) as an anionic surfactant, 0.004 parts of 5% potassium hydroxide aqueous solution, and 0.42 parts of water were mixed and crushed by a ball mill (trade name "magnetic ball mill", manufactured by Nippon To Science Co., Ltd.), thereby obtaining an aqueous dispersion of sulfur. In addition, as the mixing conditions using the ball mill, ceramic magnetic balls of Φ10 mm to Φ35 mm (a mixture of ceramic magnetic balls of Φ10 mm, Φ15 mm, Φ20 mm, Φ25 mm, Φ30 mm and Φ35 mm) were used, and the mixing was carried out at 50 rpm for 72 hours.

[0184] (Preparation of aqueous dispersion of xanthogenic acid compound)

[0185] 2.5 parts of zinc diisopropyl xanthate (trade name "NOCCELER ZIX", manufactured by Ouchi Shinko Chemical Industry Co., Ltd., volume average particle size: 14 μm, 95% volume cumulative diameter (D95): 55 μm) as a xanthogenic acid compound, 0.45 parts (18.0 parts per 100 parts of zinc diisopropyl xanthate) of polyoxyethylene distyrenated phenyl ether (trade name "EMULGENA-60", manufactured by Kao Corporation) as a nonionic surfactant, and 2.05 parts of water were mixed and crushed by a ball mill (trade name "Magnetic Ball Mill", manufactured by Nippon To Science Co., Ltd.), thereby obtaining an aqueous dispersion of the xanthogenic acid compound. In addition, as the mixing conditions using the ball mill, ceramic magnetic balls of Φ10 mm to Φ35 mm (a mixture of ceramic magnetic balls of Φ10 mm, Φ15 mm, Φ20 mm, Φ25 mm, Φ30 mm and Φ35 mm) were used, and the mixing was carried out at 50 rpm for 72 hours.

[0186] (Preparation of latex composition)

[0187] While stirring the carboxyl-modified synthetic polyisoprene latex (A-1) obtained above, ion exchange water was added so as to adjust the solid content concentration to 40 wt %. Next, 0.5 parts of the sulfur aqueous dispersion prepared above in terms of sulfur and 2.5 parts of the xanthogenic acid compound aqueous dispersion in terms of diisopropyl zinc xanthate were added to 100 parts of the carboxyl-modified synthetic polyisoprene in the carboxyl-modified synthetic polyisoprene latex (A-1) whose solid content concentration was adjusted.

[0188] Then, while stirring the obtained mixture, an aqueous dispersion of each compounding agent was added to 100 parts of the carboxyl-modified synthetic polyisoprene in the mixture, in terms of solid content conversion, 1.5 parts of zinc oxide as an activator, 1.5 parts of 2,2'-methylenebis(4-methyl-6-tert-butylphenol) (trade name "NOCRAC NS-6", manufactured by Ouchi Shinko Chemical Industry Co., Ltd., molecular weight 340, an antioxidant as an aromatic compound (a-3) having a hindered phenol structure on each of the two benzene rings constituting the diphenylmethane skeleton), 6-(4-hydroxy-3,5-di-tert-butylanilino)-2,4-bis(octylthio)-1,3,5-triazine (trade name "IRGANOX 565", manufactured by BASF, with a molecular weight of 589, an antioxidant as an aromatic compound (b-1) having one phenolic hydroxyl group and one or more -NH- bonds) was added in an amount of 0.5 parts, and then the mixture was aged (pre-vulcanized) for 48 hours in a constant temperature water bath adjusted to 25°C to obtain a latex composition.

[0189] (Manufacturing of Impregnated Molded Article)

[0190] A commercially available ceramic hand-shaped mold (manufactured by Shinko Co., Ltd.) was cleaned, preheated in an oven at 70° C., immersed in a coagulant aqueous solution containing 18% by weight of calcium nitrate and 0.05% by weight of polyoxyethylene lauryl ether (trade name "EMULGEN 109P", manufactured by Kao Corporation) for 5 seconds, and then removed from the coagulant aqueous solution. Next, the hand-shaped mold was dried in an oven at 70° C. for more than 30 minutes to allow the coagulant to adhere to the hand-shaped mold, thereby covering the hand-shaped mold with the coagulant.

[0191] Then, the hand-shaped mold coated with the coagulant was taken out from the oven and immersed in the 48-hour aged latex composition obtained above for 10 seconds. Next, the hand-shaped mold was air-dried at room temperature for 10 minutes and then immersed in warm water at 60°C for 5 minutes to dissolve water-soluble impurities and form a dip-molded layer on the hand-shaped mold. Then, the dip-molded layer formed on the hand-shaped mold was heated in an oven at a temperature of 130°C for 30 minutes to vulcanize it, and then cooled to room temperature, talc was spread and peeled off from the hand-shaped mold to obtain a dip-molded body in the shape of a glove. Then, the obtained dip-molded body was used to measure the thickness, tensile strength and tear strength of the dip-molded body according to the above method. The results are shown in Table 1.

[0192] <Example 2>

[0193] The same procedure as in Example 1 was performed except that the aqueous dispersion of 6-(4-hydroxy-3,5-di-tert-butylanilino)-2,4-bis(octylthio)-1,3,5-triazine was not added and the amount of the aqueous dispersion of 2,2'-methylenebis(4-methyl-6-tert-butylphenol) added was changed from 1.5 parts to 2.0 parts in terms of solid content conversion, to obtain an impregnated molded body. The obtained impregnated molded body was used to measure the thickness, tensile strength, and tear strength of the impregnated molded body according to the above method. The results are shown in Table 1.

[0194] <Example 3>

[0195] Instead of adding the aqueous dispersion of 2,2'-methylenebis(4-methyl-6-tert-butylphenol) and the aqueous dispersion of 6-(4-hydroxy-3,5-di-tert-butylanilino)-2,4-bis(octylthio)-1,3,5-triazine, an aqueous dispersion of 4,4'-methylenebis(2,6-di-tert-butylphenol) (trade name "Ethanox 702", manufactured by Ethyl Corporation, molecular weight 425, antioxidant for aromatic compounds (a-3) having a hindered phenol structure on each of the two benzene rings constituting the diphenylmethane skeleton) was added in an amount of 2.0 parts in terms of solid content relative to 100 parts of the carboxyl-modified synthetic polyisoprene in the mixture, and the same procedure as in Example 1 was performed to obtain an impregnated molded body. Using the obtained impregnated molded body, the thickness, tensile strength and tear strength of the impregnated molded body were measured according to the above method. The results are shown in Table 1.

[0196] <Example 4>

[0197] The same procedure as in Example 3 was followed except that the latex (A-2) of carboxyl-modified synthetic polyisoprene was used instead of the latex (A-1) of carboxyl-modified synthetic polyisoprene to obtain an impregnated molded article. The thickness, tensile strength, and tear strength of the impregnated molded article were measured by the above-mentioned method using the obtained impregnated molded article. The results are shown in Table 1.

[0198] <Example 5>

[0199] The same procedure as in Example 3 was followed except that the solid content concentration of the latex (A-1) of carboxyl-modified synthetic polyisoprene was changed from 40 wt % to 30 wt %. A dip molded body was obtained. The thickness, tensile strength and tear strength of the dip molded body were measured by the above-mentioned method using the obtained dip molded body. The results are shown in Table 1.

[0200] <Comparative Example 1>

[0201] The same procedure as in Example 1 was performed except that an aqueous dispersion of a butylated reaction product of p-cresol and dicyclopentadiene (trade name "Wingstay L, manufactured by Goodyear Tire & Rubber Company, molecular weight 650, melting point 115° C.) was added in an amount of 2.0 parts in terms of solid content relative to 100 parts of the carboxyl-modified synthetic polyisoprene in the mixture instead of the aqueous dispersion of 2,2'-methylenebis(4-methyl-6-tert-butylphenol) and the aqueous dispersion of 6-(4-hydroxy-3,5-di-tert-butylanilino)-2,4-bis(octylthio)-1,3,5-triazine. An impregnated molded body was obtained. The obtained impregnated molded body was used to measure the thickness, tensile strength, and tear strength of the impregnated molded body according to the above-mentioned method. The results are shown in Table 1.

[0202] <Comparative Example 2>

[0203] The same procedure as in Comparative Example 1 was followed except that the solid content concentration of the latex (A-1) of carboxyl-modified synthetic polyisoprene was changed from 40 wt % to 50 wt %. A dip-molded body was obtained. The thickness, tensile strength, and tear strength of the dip-molded body were measured by the above-mentioned method using the obtained dip-molded body. The results are shown in Table 1.

[0204] <Comparative Example 3>

[0205] The same procedure as in Example 1 was carried out except that an aqueous dispersion of pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] (trade name "IRGANOX 1010, manufactured by BASF, molecular weight 1120) was added in an amount of 2.0 parts in terms of solid content relative to 100 parts of the carboxyl-modified synthetic polyisoprene in the mixture instead of the aqueous dispersion of 2,2'-methylenebis(4-methyl-6-tert-butylphenol) and the aqueous dispersion of 6-(4-hydroxy-3,5-di-tert-butylanilino)-2,4-bis(octylthio)-1,3,5-triazine. An impregnated molded body was obtained. The thickness, tensile strength, and tear strength of the impregnated molded body were measured by the above-mentioned method using the obtained impregnated molded body. The results are shown in Table 1.

[0206] <Comparative Example 4>

[0207] The same procedure as in Example 1 was performed except that 2.0 parts of dibutylhydroxytoluene (molecular weight 220) was added in terms of solid content relative to 100 parts of carboxyl-modified synthetic polyisoprene in the mixture instead of adding the aqueous dispersion of 2,2'-methylenebis(4-methyl-6-tert-butylphenol) and the aqueous dispersion of 6-(4-hydroxy-3,5-di-tert-butylanilino)-2,4-bis(octylthio)-1,3,5-triazine. The obtained impregnation molded body was used to measure the thickness, tensile strength, and tear strength of the impregnation molded body according to the above method. The results are shown in Table 1.

[0208] [Table 1]

[0209]

[0210] As shown in Table 1, the reduction in mechanical strength of a film-formed body having a thickness of 20 to 300 μm obtained by using a latex composition containing a conjugated diene polymer, a sulfur-based vulcanizing agent, a vulcanization accelerator, and an antioxidant, wherein the antioxidant is at least one selected from a phenolic antioxidant and a quinoline antioxidant, and the molecular weight of the antioxidant is 300 to 600 when stored at 70°C is suppressed (Examples 1 to 5).

[0211] On the other hand, the film formed body obtained by using an antioxidant with a molecular weight of less than 300 or greater than 600 has a large decrease in mechanical strength when stored at 70°C (Comparative Examples 1, 3, and 4). In addition, the film formed body obtained by using an antioxidant with a molecular weight greater than 600 has a large decrease in mechanical strength when stored at 70°C even when the thickness is greater than 300 mm (Comparative Example 2).

Claims

1. A film-formed product having a thickness of 20 to 300 μm obtained by using a latex composition, The latex composition contains a latex of a conjugated diene polymer, a sulfur-based vulcanizing agent, a vulcanization accelerator, an antioxidant, and zinc oxide. The latex of the conjugated diene polymer is a latex of synthetic polyisoprene or a latex of a styrene-isoprene-styrene block copolymer. The antioxidant is a phenolic antioxidant, and the molecular weight of the antioxidant is 300 to 600. The content of the sulfur-based vulcanizing agent in the latex composition is 0.1 to 1.2 parts by weight relative to 100 parts by weight of the conjugated diene polymer in the latex composition.

2. The film formed body according to claim 1, wherein The antioxidant contains at least an aromatic compound (a) having two or more phenolic hydroxyl groups.

3. The film formed body according to claim 1 or 2, wherein The antioxidant contains at least an aromatic compound (a-1) having two or more hindered phenol structures.

4. The film formed body according to claim 1 or 2, wherein The antioxidant contains at least an aromatic compound (a-2) having two or more hindered phenol structures and a diphenylmethane skeleton.

5. The film formed body according to claim 1 or 2, wherein The antioxidant comprises an aromatic compound (a) having two or more phenolic hydroxyl groups, and an aromatic compound (b-1) having one phenolic hydroxyl group and one or more -NH- bonds.

6. The film formed body according to claim 1 or 2, wherein The latex of the conjugated diene polymer is a latex of synthetic polyisoprene.

7. The film formed body according to claim 1 or 2, wherein The conjugated diene polymer latex is a carboxyl-modified conjugated diene polymer latex.

8. The film formed body according to claim 1 or 2, wherein The conjugated diene polymer has a swelling index (SI) of 105 to 300%.

9. The film formed body according to claim 1 or 2, wherein The vulcanization accelerator is a xanthate compound.

Citation Information

Patent Citations

  • Dip molding composition and dip molded article

    JP2011219543A

  • Thin film-like rubber product

    JP2002125985A

  • Soft nitrile zinc oxide-free medical glove

    JP2003041410A

  • Rubber latex, rubber latex for dip molding, and dip-molded article

    US20100204397A1